2006
DOI: 10.1007/s00221-006-0440-8
|View full text |Cite
|
Sign up to set email alerts
|

Extensive training of elementary finger tapping movements changes the pattern of motor cortex excitability

Abstract: There is evidence of a strong capacity for functional and structural reorganization in the human motor system. However, past research has focused mainly on complex movement sequences over rather short training durations. In this study we investigated changes in corticospinal excitability associated with longer training of elementary, maximum-speed tapping movements. All participating subjects were consistent right-handers and were trained using either the right (experiment 1) or the left thumb (experiment 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 78 publications
3
89
2
1
Order By: Relevance
“…The present data support findings of recent studies that unilateral ballistic motor training can cause bilateral changes in corticospinal excitability (10,20), although the previous studies did not assess performance transfer. Interestingly, Duque et al (10) reported a reduction in MEP amplitude in the untrained hand in response to unilateral finger abduction practice in which they viewed their moving finger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present data support findings of recent studies that unilateral ballistic motor training can cause bilateral changes in corticospinal excitability (10,20), although the previous studies did not assess performance transfer. Interestingly, Duque et al (10) reported a reduction in MEP amplitude in the untrained hand in response to unilateral finger abduction practice in which they viewed their moving finger.…”
Section: Discussionsupporting
confidence: 91%
“…Thus the data do not provide conclusive evidence that the spillover hypothesis is a mechanism that contributes to the cross-transfer of ballistic motor skill. They do, however, extend recent evidence that unilateral ballistic practice can cause lasting effects on ipsilateral cortical excitability (10,20).…”
Section: Discussioncontrasting
confidence: 43%
“…Given this, our results are not inconsistent with previous findings, and they underscore the importance of considering the entire handedness and laterality spectrum. It is also not clear whether these handedness effects arise during development or are a function of extended experience, particularly given evidence that practice results in increased corticospinal excitability in both hemispheres (both contra-and ipsilateral to practice) (Koeneke et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using neuroimaging techniques have reported that motor training composed of finger movements, such as piano play or SRT tasks, results in performance improvement and characteristic reorganizational changes in the motor cortex [6][7][8][9] . These studies have suggested that the connection between neural network and motor skill learning is related to the finding that the extent of specific cortical representation can increase or decrease during learning.…”
Section: Introductionmentioning
confidence: 99%